2023
DOI: 10.1002/cft2.20207
|View full text |Cite
|
Sign up to set email alerts
|

Layered‐residual herbicide programs for waterhemp control in glufosinate‐resistant soybean

Abstract: Core Ideas Glufosinate is an important POST herbicide for waterhemp control in glufosinate‐resistant soybean. The layered‐residual herbicide approach improved season‐long waterhemp control. Glufosinate POST combined with layered soil residual herbicides improved season‐long waterhemp control. Glufosinate is an important POST herbicide for waterhemp control in glufosinate‐resistant soybean. The layered‐residual herbicide approach improved season‐long waterhemp control. Glufosinate POST combined with layered so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Means were compared by grouping letters using emmeans and cld functions of "emmeans" (Lenth et al., 2021) and "multcomp" (Hothorn et al., 2008) packages. Herein, weed control results are discussed based on “effective control” (>90% control of a species), which is common procedure in chemical weed control research to support management recommendations (Arneson et al., 2020; Etheridge et al., 2011; Werle et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Means were compared by grouping letters using emmeans and cld functions of "emmeans" (Lenth et al., 2021) and "multcomp" (Hothorn et al., 2008) packages. Herein, weed control results are discussed based on “effective control” (>90% control of a species), which is common procedure in chemical weed control research to support management recommendations (Arneson et al., 2020; Etheridge et al., 2011; Werle et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Results of the current study indicate that no single active ingredient POST herbicide provided complete control of established waterhemp plants at Brooklyn, WI. Our previous research demonstrated that herbicides with soil residual activity are effective tools for waterhemp and can provide additional sites of action toward more effective chemical weed management programs (Arneson et al., 2019; Ribeiro et al., 2022). Weed management programs containing multiple effective herbicide sites of action pre‐ and post‐emergence (Hydrick & Shaw, 1994; Kumar et al., 2021) accompanied by non‐chemical strategies (i.e., cover crops, narrow row spacing, harvest weed seed control) are recommended to extend the spectrum of chemical weed control and reduce the risk of selection of further herbicide‐resistant biotypes for both giant ragweed and waterhemp in Wisconsin and beyond.…”
Section: Soil Conditions Site and Year Average Weed Density M−2 Her...mentioning
confidence: 99%